(untitled) (Research, Society and Development, 2020)
Objectives: to understand how the elderly mean their transformations in relation to temporality and the ontological condition of being-elderly. Methodology: Exploratory-descriptive, qualitative study, according to the presuppositions of the phenomenological approach in Heidegger. Results: Fifteen elderly, 11 females and 4 males, aged between 61 and 89 years, all retired, were interviewed. Most of them live with relatives and are illiterate. The results extracted from the speeches revealed the following units of meaning: 1- Recognizing the elderly in their existentiality; 2 - Being in the world as an old man; 3- The aging and the having-to-be for death. Conclusion: The understanding of aging under the perception of the elderly, so that their real needs are known and consequently they can intervene in an effective way, generating quality of life. Thus, it is necessary to reconsider the way of treating the elderly, as well as the assistance provided in the health and society as a whole.